Intensitas Serangan Penyakit Karat Daun (Phakopsora pachyrhizi) Pada Beberapa Varietas Kedelai (Glycine max (L). Merril) - Fitri Mei Arini, Silvia; Arya Pamungkas, Muhammad (JURNAL AGROPLANT, 2025)
This study aims to examine the intensity of Rust Disease (Phakopsora pachyrhhizi) and the resistance of soybean varieties (Glycine max (L.) Merrill) to crop yields. This study uses a Random Group Design (RAK) consisting of four varieties of soybeans, namely Wilis, Malabar, Ringgit and Dega-1. With 4 replicates and each replicate 5 plant samples were taken. The basic fertilizer used in accordance with the technical instructions of the national soybean consortium is 75 kg ZA + 100 kg SP36 + 75 kg KCl/ha + 5 tons of manure/ha. The observation data was analyzed using Analysis of Variance (F test). If the results show a real influence, the Smallest Real Difference (BNT) test of 5% will be continued. The study showed that the intensity of leaf rust attack and soybean resistance resulted in a dry weight of 19.70 g of Ringgit varieties, 18.05 g of Wilis, 17.05 g higher than that of the Dega-1 variety which weighed 6.25 g.